Conformation-Dependent High-Affinity Potent Ricin-Neutralizing Monoclonal Antibodies. (26th December 2012) - Hu, Wei-Gang; Yin, Junfei; Chau, Damon; Hu, Charles Chen; Lillico, Dustin; Yu, Justin; Negrych, Laurel M.; Cherwonogrodzky, John W.
Abstract : Ricin is a potential biothreat agent with no approved antidote available for ricin poisoning. The aim of this study was to develop potent antibody-based antiricin antidotes. Four strong ricin resistant hybridoma clones secreting antiricin monoclonal antibodies (mAbs) were developed. All four mAbs are bound to conformational epitopes of ricin toxin B (RTB) with high affinity (K D values from 2.55 to 36.27 nM). RTB not only triggers cellular uptake of ricin, but also facilitates transport of the ricin toxin A (RTA) from the endoplasmic reticulum to the cytosol, where RTA exerts its toxic activity. The four mAbs were found to have potent ricin-neutralizing capacities and synergistic effects among them as determined by an in vitro neutralization assay. In vivo protection assay demonstrated that all four mAbs had strong efficacy against ricin challenges. D9 was found to be exceptionally effective. Intraperitoneal (i.p.) administration of D9, at a dose of 5  μ g, 6 weeks before or 6 hours after an i.p. challenge with 5 × LD50 of ricin was able to protect or rescue 100% of the mice, indicating that mAb D9 is an excellent candidate to be developed as a potent antidote against ricin poisoning for both prophylactic and therapeutic purposes.